The streamlined allostatic load index: a replication of study results - Mauss, Daniel; Jarczok, Marc N.; Fischer, Joachim E. (Stress, 2016)
According to the World Health Organization stress in the workplace is becoming a major challenge of employers worldwide. While perceived stress levels can be assessed by questionnaires there is growing evidence that stress-related wear and tear of our body can be measured by the Allostatic Load Index (ALI). In a sample of 12,477 German industrial employees (19.6% female, 18-65 years) self-rated stress was explored by the effort-reward imbalance (ERI) questionnaire. A voluntary health check included biomarkers such as diastolic blood pressure, waist circumference, glycosylated hemoglobin, low-density lipoprotein, and heart rate variability. Based on predefined subclinical cutoff values, a 5-variable ALI was calculated. Differences in ALI according to low (ERI ≤1.0) and high (ERI >1.0) stress levels were tested. The association of ERI and ALI was explored using logistic regression analysis controlling for multiple confounders. Employees perceiving high stress levels showed significant higher ALI scores (p < .001) compared to lower stressed employees. This association was stronger in men and independent of age. ALI was associated with work stress in adjusted models (OR 1.18 ± .08 [95% CI 1.03, 1.36]; p < .05). This study replicates former results in a large sample of industrial employees indicating that work stress is associated with a short form ALI.